2015
DOI: 10.1021/acs.est.5b01893
|View full text |Cite
|
Sign up to set email alerts
|

Evidencing the Impact of Coastal Contaminated Sediments on Mussels Through Pb Stable Isotopes Composition

Abstract: Heavily contaminated sediments are a serious concern for ecosystem quality, especially in coastal areas, where vulnerability is high due to intense anthropogenic pressure. Surface sediments (54 stations), 50 cm interface cores (five specific stations), river particles, coal and bulk Pb plate from past French Navy activities, seawater and mussels were collected in Toulon Bay (NW Mediterranean Sea). Lead content and Pb stable isotope composition have evidenced the direct impact of sediment pollution stock on bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 67 publications
8
48
0
Order By: Relevance
“…Several studies have reported high concentrations of trace metals, metalloids and organometallics during Toulon Bay seabed disturbances (Cossa et al, 2014;Dang et al, 2015a, Pougnet et al,2014Tessier et al,2011). In addition, Dang et al (2015b) demonstrated that Pb was significantly released in seawater and further transferred to organisms such as mussels during resuspension experiments on surface and deep sediments from Toulon Bay. Nevertheless, to our knowledge, no data are available describing PAH remobilization during sediment resuspension events in such a strongly dredged and multi-contaminated area.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have reported high concentrations of trace metals, metalloids and organometallics during Toulon Bay seabed disturbances (Cossa et al, 2014;Dang et al, 2015a, Pougnet et al,2014Tessier et al,2011). In addition, Dang et al (2015b) demonstrated that Pb was significantly released in seawater and further transferred to organisms such as mussels during resuspension experiments on surface and deep sediments from Toulon Bay. Nevertheless, to our knowledge, no data are available describing PAH remobilization during sediment resuspension events in such a strongly dredged and multi-contaminated area.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, in the present study, we carried out supplementary experiments simulating the resuspension of surface and deep sediments in Toulon Bay, as proposed by Dang et al (2015b)…”
Section: Introductionmentioning
confidence: 99%
“…The very short residence time of Pb in the troposphere (less than a week; Moore et al, 1973;Turekian et al, 1977) leads to a near-instantaneous change in Mediterranean Sea Pb (Nicolas et al, 1994). Consequently, core top sediment Pb isotope compositions are not necessarily expected to reflect the composition of modern seawater (e.g., Alleman et al, 2000;Huy et al, 2015;Kamenov et al, 2009), and correspondingly, there is a paucity of information in the literature dealing with Pb isotope compositions in marginal Mediterranean sediment porewaters. However, in addition to these studies which indicate that Pb mobility is low, a few have shown results consistent with our assumption of substantial seawater control.…”
Section: 1029/2018pa003538mentioning
confidence: 99%
“…In these situations, stable Pb isotope ratios provide an additional means of Pb source discrimination and have been applied successfully in a range of sedimentary/environmental settings (e.g. [27][28][29][30][31][32][33][34]). Ultrahigh precision, double-spike mass spectrometry stable Pb isotope data for the 2014 Hythe core (Figure 7) show a gradual reduction in 206 Pb/ 207 Pb ratio from core base upwards (consistent with studies from other sedimentary settings in the UK (e.g.…”
Section: Figurementioning
confidence: 99%